Real-World Epidemiology, Clinical and Economic Burden of Chronic Hepatitis B in Japan: A Retrospective Study Using JMDC Claims Database - Takeji Umemura; Kittima Wattanakamolkul; Yoshikazu Nakayama; Yasushi Takahashi; Urbano Sbarigia; Lim KyungHwa; Angelina Villasis-Keever; Martina Furegato; Laurène Gautier; Gregoire Nowacki; Jessica Azzi; David Bin-Chia Wu (Infectious Diseases and Therapy, 2023)
Abstract Introduction Chronic hepatitis B (CHB) is one of the world's major healthcare problems, especially in the Western Pacific regions. This study describes the prevalence, incidence, treatment profiles and clinical and economic burden of chronic hepatitis B patients in Japan using the Japan Medical Data Center (JMDC) Claims Database. Methods This is a retrospective observational study. Prevalence cases were identified as patients with ≥ 1 inpatient or ≥ 2 outpatient CHB diagnoses and ≥ 2 records for hepatitis B tests or ≥ 1 prescription for CHB treatment between January 2010 and December 2019. Newly diagnosed CHB patients were defined as patients diagnosed from 2010 to 2018 with no history of the disease up to 2 years prior to the diagnosis. The index date is defined as the first CHB diagnosis day. We only used patients’ data with ≥ 1-year post-index date. Results We identified 13,061 CHB prevalent cases (2010–2019), yielding a crude period prevalence of 0.32%. Newly diagnosed CHB patients (n = 1973; median age 52 years) were followed for a median period of 3.1 years, during which 15% received a CHB treatment. Entecavir was the most common first treatment (66%). During this period, 3.4% of the patients developed compensated cirrhosis (CC), 1.5% decompensated cirrhosis (DC) and 3.0% hepatocellular carcinoma (HCC). Around 43.3% of CHB patients were hospitalized at least once. Hospitalizations, treatment rates, serologic testing and screening for liver diseases increased as the severity of the disease progressed. The average total healthcare cost was 870,568 JPY (7779 USD) per person per year. DC and HCC resulted in the highest management costs. Conclusions Chronic hepatitis B represents a high clinical and economic burden for patients and caregivers, given its morbidity and associated costs.